Proceedings of the Fourth International Conference on Animal-Computer Interaction 2017
DOI: 10.1145/3152130.3152144
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethological Observation for Measuring Animal Reactions to Biotelemetry Devices

Abstract: This paper presents a methodological approach used to assess the wearability of biotelemetry devices in animals. A detailed protocol to gather quantitative and qualitative ethological observations was adapted and tested in an experimental study of 13 cat participants wearing two different GPS devices. The aim was twofold: firstly, to ascertain the potential interference generated by the devices on the animal body and behaviour by quantifying and characterising it; secondly, to individuate device features poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…Most cats would not be bothered". This is in contrast with empirical evidence from Paci et al [26] which demonstrated, through systematic observations of cats during their daily activities, that cats can have adverse reactions towards a body-attached device. P11's ability to observe their cat while this wore the device was limited, since the animal was fitted with the GPS soon before leaving home and released upon returning home.…”
Section: Subtheme 2 -Difficulty Of Aligning With Animal Perspectivecontrasting
confidence: 83%
See 1 more Smart Citation
“…Most cats would not be bothered". This is in contrast with empirical evidence from Paci et al [26] which demonstrated, through systematic observations of cats during their daily activities, that cats can have adverse reactions towards a body-attached device. P11's ability to observe their cat while this wore the device was limited, since the animal was fitted with the GPS soon before leaving home and released upon returning home.…”
Section: Subtheme 2 -Difficulty Of Aligning With Animal Perspectivecontrasting
confidence: 83%
“…Initially, we based our WCF on the model from Preece et al ([27], pp. [19][20][21][22][23][24][25][26][27][28][29][30], who promote the use of conceptual tools such as design principles, usability goals, and user experience goals to design for good user experience.…”
Section: Framework-based Approachmentioning
confidence: 99%
“…Future functionalities and trade-offs. The need to keep the dimensions and weight of tracking devices to a minimum for welfare reasons means that these devices have limited battery capacity [19], while at the same time having to feed a technology that is notoriously power-hungry. Participants were aware of the need to find trade-offs between monitoring their cats as frequently as they wished and limiting their usage to extend the battery life in case of emergency.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the usefulness of the WCF as a design tool, we conducted three separate one-day workshops during which three teams of designers respectively were asked to use the WCF to establish design requirements for a collared tracking device for domestic cats. Cats were chosen as a model species due to their ubiquity and tractability but also relative independence, and for consistency with the study conducted by Paci et al [7]. The collaborative requirements workshops [3] were organized following a template derived from the +ACUMEN-IDEO.org course for roughly prototyping a physical artefact [4].…”
Section: Collaborative Requirements Workhopsmentioning
confidence: 99%
“…In a recent study, Paci et al [7] used specific behavioral indicators to evaluate the response of domestic cats to two offthe-shelf collared devices marketed as cat-friendly. The authors found increments of head shaking and scratching (regarded as indicators of discomfort) in the area of attachment, and peculiar responses (such as cuffing and biting) directed at the device.…”
Section: Introductionmentioning
confidence: 99%